Piet Mondrian’s neo-plastic compositions (1917-1944) and his six principles of neo-plasticism: An analysis of his aesthetic ideas based on a study of his essays and paintings / Ali Fallahzadeh - Ali , Fallahzadeh (2020)

(untitled)
Amongst the modern artists of the beginning of the 20th century, Dutch painter Piet Mondrian (1872-1944) is considered a pioneer of pure abstract painting. The result of his consistent intuitive experimentations on canvas during the 1910’s was the proposal of his new artistic style in 1919 called Neo-Plasticism, nieuwe beelding in Dutch. Throughout his Neo-Plastic period (1919-1944), he aimed to depict a universal expression of ‘equilibrium’ (new term for harmony) and a vital rhythm among his universal elements of painting called plastic means or means of imaging. Besides being a pure abstract painter, Mondrian was also a prolific writer of his theories. His theoretical writings, the majority of them written in the form of essays, articles, and notes, are indeed posterior outcome of his intuitive experimentations on his canvases. Scholars generally agree that his writings outline the evolution of his artistic vision of Neo-Plasticism. Considering the importance of Mondrian as an iconic pure abstract painter in the history of modern art, many scholars have emphasized on the contribution of this Dutch painter to modern art. However, previous researches did contextual analysis investigating his Neo-Plastic art and theory in relation to his artistic and philosophical influences such as De Stijl, Theosophy, Hegel, and Platonism. Contrary to the previous researches, this thesis looks at Mondrian’s writings and paintings, focusing on the evolution of his aesthetic ideas based on his artistic experimentation on the canvas. First, in order to explain the development of Mondrian’s artistic vision, his paintings were divided into three stylistic periods. Then, the important concepts of Neo-Plasticism found in his six principles of Neo-Plasticism are identified and compared to the paintings of the three periods. Secondly, the theoretical development of these concepts is analyzed, using both Mondrian’s paintings and texts, produced and written roughly at the same time. This thesis shows that a thorough examination of an experimental modern artists’ writings, like those of Mondrian, although difficult and complex, in parallel with a visual study of his artistic experimentation on the canvas can expand our understanding of their aesthetic evolution and bring something new to Art History of Modern Art.